2008
DOI: 10.1097/mcc.0b013e3282fc9a9c
|View full text |Cite
|
Sign up to set email alerts
|

Predicting defibrillation success

Abstract: Recent results question the ventricular fibrillation feature analysis as a reliable tool to estimate the duration of human cardiac arrest. Animal and clinical studies confirmed that ventricular fibrillation waveform analysis contains information to reliably predict the countershock success rate and further improved countershock outcome prediction. Prospective clinical studies are highly warranted to demonstrate that ventricular fibrillation waveform analysis definitely improves survival after cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Characteristics of the VF waveform have also been associated with defibrillation success 2,3,4 . This relation is (partly) driven by arrest duration, as was shown in a study in animals that reported that an independent association between VF characteristics and shock success could only be demonstrated if VF duration was not included in the multivariate model 6 .…”
Section: Vf Waveform Characteristics and Defibrillation Successmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the VF waveform have also been associated with defibrillation success 2,3,4 . This relation is (partly) driven by arrest duration, as was shown in a study in animals that reported that an independent association between VF characteristics and shock success could only be demonstrated if VF duration was not included in the multivariate model 6 .…”
Section: Vf Waveform Characteristics and Defibrillation Successmentioning
confidence: 99%
“…With delivery of chest compressions shock success may be improved, and the coarseness of the VF waveform seems to increase concurrently 7,8 . In view of these findings, VF waveform characteristics have been regarded as markers of myocardial readiness for successful defibrillation, and have been studied to guide shock delivery 2,8 . However, retrospective studies in humans on the predictive value of VF analysis for shock success showed variable results 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Human studies indicate that the rate indicated for the termination of rapid, irregular polymorphic ventricular tachycardia and pulseless ventricular tachycardia. 11 Human studies indicate that the rate indicated for the termination of rapid, irregular polymorphic ventricular tachycardia and pulseless ventricular tachycardia.…”
Section: Complicationsmentioning
confidence: 99%
“…Over the years, various initiatives have been taken to improve outcome after out-of-hospital cardiac arrest (OHCA) [1,2]. For patients with ventricular fibrillation (VF), one of the proposed strategies involves guidance of chest compressions and shock deliveries based on analysis of the VF waveform [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%